A Study Of Semantic Roles in two Excerpts From Amma Darko’s Amma Darko’s Amma Darko’s Amma Darko’s Faceless FacelessFaceless Fa - YOKOSSI, Tchorkpa Daniel (My University, 2018)
The paper closely examines semantic roles in two extracts taken from Amma Darko’s Faceless to uncover both the writer’s ideological perspectives and the different underlying meanings hidden between lines in the selected passages. To reach this aim, the selection of the extracts has been based on the criterion that they yield to the study in hand. Moreover, the research has appealed to both the quantitative and the qualitative methods. To be more specific, practical statistics of the technical analysis data carried out have been drawn up and findings have been interpreted as well, following both above mentioned methods respectively. The results of the findings have, among others, revealed that semantic roles also referred to as thematic roles are unquestionable linguistic tools for deep meanings making in written language. A glance at the interpretation section tells more about this. Furthermore the study has uncovered that Amma Darko’s, Faceless is, for one, directed at raising African families’ consciousness for better social, material and financial living condition. Ultimately, the scholarship opens up to such further research horizons as discourse-semantic analysis, lexico- grammatical analysis, and register analysis.
Keywords: semantic-roles; participant; thematic grid; prototype